Medetomidine - ketamine anaesthesia in canine and its reversal by atipamezole - Tiwari, S K; Roy, S; Mishra, U K (The Indian Journal of Animal Sciences, 2012)
Intramuscular administration of medetomidine @ 20µg/kg and ketamine @ 50mg/kg IV in atropine sulphate (0.02 mg/kg IM) premedicated 36 healthy dogs resulted in onset of anaesthesia in 1.98±0.26 min, duration of anaesthesia of 42.86±2.80 min with complete recovery in 94.14±6.l8 min. Transient respiratory depression, increased heart rate followed by decrease and slight hypothermia were observed, The sedative and physiological effects were completely antagonized by IV administration of atipamezole (@ 20µg/kg IV) with mean walking time of 2.36±0.18 min. Thus atropine-medetomidine-ketamine combination Can safely be used in dogs as it caused rapid onset, prolonged anaesthesia with smooth and uneventful recovery, and its total reversibility permits optimum control of anaesthesia.